On Some Properties of Programming Problems in Parametric form Pertaining to Fractional Programming - Jagannathan, R. (Management Science, 1966)
This paper presents results which apply to convex programming problem in parametric form. The results secured are also related to the problem of fractional programming in a way which indicates computational possibilities for the latter class of problems. The results are extended to general non-linear programming problems with special reference to continuous criterion functions. As a particular case, the linear fractional programming problem is considered and, in conclusion, the results secured here are pointed up by reference to existing algorithms for the latter class of problems.